Analisis Implementasi Manajemen Risiko Berbasis Pendekatan Coso Erm, Swot, Dan Matriks Risiko Pada Auraku Florist - Ashilah Fauziyah; Siti Azmi Nur Islami; Ummu Mahmudah; Yesica Maulina; Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze risk management in the micro-business Auraku Florist using the COSO Enterprise Risk Management (ERM) approach combined with SWOT analysis and Risk Matrix. Auraku Florist is a flower arrangement service business that serves orders directly and through digital media, thus potentially facing various operational and non-operational risks. This study uses a qualitative descriptive method through observation and interviews to identify and evaluate risks that can affect business continuity. The results show that there are 30 risk events, consisting of 7 high category risks, 20 medium category risks, and 3 low category risks. High category risks mainly originate from financial, operational, and human resource aspects, such as limited capital, cash flow management, quickly wilting flowers, and employee absenteeism. The dominant management strategy applied is risk reduction, followed by risk sharing, risk avoidance, and risk acceptance according to each risk level. The application of the COSO ERM framework helps Auraku Florist in identifying, assessing, and managing risks more systematically and sustainably. This effort is expected to increase the effectiveness of risk control and support the sustainability of business operations amidst the increasingly competitive florist industry.